Grass pea natural variation reveals oligogenic resistance to Fusarium oxysporum f. sp. pisi. Issue 3 (7th October 2021) - Sampaio, Ana Margarida; Alves, Mara Lisa; Pereira, Priscila; Valiollahi, Ehsan; Santos, Carmen; Šatović, Zlatko; Rubiales, Diego; Araújo, Susana de Sousa; van Eeuwijk, Fred; Vaz Patto, Maria Carlota
Abstract: Grass pea ( Lathyrus sativus L.) is an annual legume species, phylogenetically close to pea ( Pisum sativum L.), that may be infected by Fusarium oxysporum f. sp. pisi ( Fop ), the causal agent of fusarium wilt in peas with vast worldwide yield losses. A range of responses varying from high resistance to susceptibility to this pathogen has been reported in grass pea germplasm. Nevertheless, the genetic basis of that diversity of responses is still unknown, hampering its breeding exploitation. To identify genomic regions controlling grass pea resistance to fusarium wilt, a genome‐wide association study approach was applied on a grass pea worldwide collection of accessions inoculated with Fop race 2. Disease responses were scored in this collection that was also subjected to high‐throughput based single nucleotide polymorphisms (SNP) screening through genotyping‐by‐sequencing. A total of 5, 651 high‐quality SNPs were considered for association mapping analysis, performed using mixed linear models accounting for population structure. Because of the absence of a fully assembled grass pea reference genome, SNP markers' genomic positions were retrieved from the pea's reference genome v1a. In total, 17 genomic regions were associated with three fusarium wilt response traits in grass pea, anticipating an oligogenic control. Seven of these regions were located on pea chromosomes 1, 6, and 7. The candidate genes underlying these regions were putatively involved in secondary and amino acid metabolism, RNA (regulation of transcription), transport, and development. This study revealed important fusarium wilt resistance favorable grass pea SNP alleles, allowing the development of molecular tools for precision disease resistance breeding. Core Ideas: The first grass pea disease resistance genome‐wide association study was conducted. Grass pea revealed an oligogenic control to fusarium wilt. 17 significantly fusarium wilt resistance associated SNPs were detected. Candidate genes were involved in secondary/amino acid metabolism, RNA, transport, and development.